1994
DOI: 10.1177/030089169408000111
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor and Estrogen and Progesterone Receptors in Breast Cancers of Premenopausal and Postmenopausal Patients

Abstract: The present findings may have significance in differentiation of postmenopausal breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…6 -9 Multivariate analyses to assess associations of age and menopausal status with other clinical and pathologic characteristics have not consistently retained either variable as an independent adverse prognosticator, 8 although several multivariate analyses have indicated that young age or premenopausal status are independent predictors of disease recurrence. 10 -13 In addition, a few studies have found that those women at the extremes of age, i.e., premenopausal women younger than 33 years of age 11 or postmenopausal women older than 80 -85 years of age, 3,14 had a worse prognosis than other age groups.Breast carcinomas in young women have been reported to express fewer estrogen receptors (ER), 10,[15][16][17][18] to have a higher index of proliferation 8,19 -22 and to be more likely to exhibit an abnormal nuclear accumulation of mutant p53 protein 8,23-26 than those in older women. Also, comparisons of the pathology of breast carcinomas have demonstrated that there is a greater proportion of high-grade carcinomas in young women (younger than 40 years) 27,28 and that special histologic types of invasive carcinoma (e.g., mucinous and papillary carcinomas) with more favorable prognoses than the more common infiltrating ductal carcinoma are more prevalent in older than younger populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 -9 Multivariate analyses to assess associations of age and menopausal status with other clinical and pathologic characteristics have not consistently retained either variable as an independent adverse prognosticator, 8 although several multivariate analyses have indicated that young age or premenopausal status are independent predictors of disease recurrence. 10 -13 In addition, a few studies have found that those women at the extremes of age, i.e., premenopausal women younger than 33 years of age 11 or postmenopausal women older than 80 -85 years of age, 3,14 had a worse prognosis than other age groups.Breast carcinomas in young women have been reported to express fewer estrogen receptors (ER), 10,[15][16][17][18] to have a higher index of proliferation 8,19 -22 and to be more likely to exhibit an abnormal nuclear accumulation of mutant p53 protein 8,23-26 than those in older women. Also, comparisons of the pathology of breast carcinomas have demonstrated that there is a greater proportion of high-grade carcinomas in young women (younger than 40 years) 27,28 and that special histologic types of invasive carcinoma (e.g., mucinous and papillary carcinomas) with more favorable prognoses than the more common infiltrating ductal carcinoma are more prevalent in older than younger populations.…”
mentioning
confidence: 99%
“…Breast carcinomas in young women have been reported to express fewer estrogen receptors (ER), 10,[15][16][17][18] to have a higher index of proliferation 8,19 -22 and to be more likely to exhibit an abnormal nuclear accumulation of mutant p53 protein 8,[23][24][25][26] than those in older women. Also, comparisons of the pathology of breast carcinomas have demonstrated that there is a greater proportion of high-grade carcinomas in young women (younger than 40 years) 27,28 and that special histologic types of invasive carcinoma (e.g., mucinous and papillary carcinomas) with more favorable prognoses than the more common infiltrating ductal carcinoma are more prevalent in older than younger populations.…”
mentioning
confidence: 99%